Oxidoreductases Involved in Cell Carbon Synthesis of Methanobacterium thermoautotrophicum - Zeikus, J. G. (1977)
Cell-free extracts of Methanobacterium thermoautotrophicum were found to contain high activities of the following oxidoreductases (at 60°C): pyruvate dehydrogenase (coenzyme A acetylating), 275 nmol/min per mg of protein; α-ketoglutarate dehydrogenase (coenzyme A acylating), 100 nmol/min per mg; fumarate reductase, 360 nmol/min per mg; malate dehydrogenase, 240 nmol/min per mg; and glyceraldehyde-3-phosphate dehydrogenase, 100 nmol/min per mg. The kinetic properties (apparent V(max) and K(M) values), pH optimum, temperature dependence of the rate, and specificity for electron acceptors/donors of the different oxidoreductases were examined. Pyruvate dehydrogenase and α-ketoglutarate dehydrogenase were shown to be two separate enzymes specific for factor 420 rather than for nicotinamide adenine dinucleotide (NAD), NADP, or ferredoxin as the electron acceptor. Both activities catalyzed the reduction of methyl viologen with the respective α-ketoacid and a coenzyme A-dependent exchange between the carboxyl group of the α-ketoacid and CO(2). The data indicate that the two enzymes are similar to pyruvate synthase and α-ketoglutarate synthase, respectively. Fumarate reductase was found in the soluble cell fraction. This enzyme activity coupled with reduced benzyl viologen as the electron donor, but reduced factor 420, NADH, or NADPH was not effective. The cells did not contain menaquinone, thus excluding this compound as the physiological electron donor for fumarate reduction. NAD was the preferred coenzyme for malate dehydrogenase, whereas NADP was preferred for glyceraldehyde-3-phosphate dehydrogenase. The organism also possessed a factor 420-dependent hydrogenase and a factor 420-linked NADP reductase. The involvement of the described oxidoreductases in cell carbon synthesis is discussed.